PENGARUH PENDIDIKAN KARYAWAN DAN PELATIHAN KARYAWAN TERHADAP KUALITAS KERJA KARYAWAN (STUDI KASUS KARYAWAN PT. ANUGRAH MANDIRI SEJATERAH) - Fauziah, Anisatul (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2024)
Competition in the current work environment is increasingly fierce, this requires companies to continuously develop their businesses to be able to compete with other companies. Therefore, company management is needed, which is usually called Human Resources Management. This research aims to determine the effect of education and training on the quality of work of employees of Pt. Anugrah Mandiri Sejaterah which is located in Getem Village, Jember Regency, either partially or simultaneously. This type of research uses quantitative descriptive methods sourced from internal data and external data that provide information about the company. Data collection methods include documentation and distributing questionnaires. The measurement scale used to determine the value of the answers given by respondents is a Likert scale with data analysis using multiple linear regression analysis. The results of the education obtained are that education partially influences the quality of employee work, training partially influences employee work quality, and simultaneously the two independent variables influence employee work quality)